Authorial Ethics : How Writers Abuse Their Calling. - Hauptman, Robert (Lexington Books, 2011)
Authorial Ethics is a study of the ways in which writers abrogate their implicit and explicit commitment to honesty and truth. It encompasses all disciplines and is both theoretical and applied.